VİYANA SATIM SÖZLEŞMESİ KAPSAMINDA SATICININ SÖZLEŞMEYİ İHLALİ HALİNDE ALICIYA TANINAN HAKLARIN İNCELENMESİ - Öztürk, Lamiha; Çobanoğlu, Yağmur (Ramazan Çakmakcı, 2020)
Birleşmiş Milletler Uluslararası Mal Satış Sözleşmeleri (CISG)uluslararası ticaret için tek tip bir çerçeve oluşturan çok taraflı bir antlaşmadır. Yasal geleneklerine veya ekonomik kalkınma düzeylerine bakılmaksızın taraf olan tüm ülkelerde eşit ve modern temel kurallar oluşturarak ticaret yapılmasını amaçlar. Bu çalışmamızda Viyana Satım Sözleşmesi kapsamında satıcının sözleşmeyi ihmal etmesi durumunda alıcının sahip olacağı haklar incelenmiştir. Bu satım sözleşmesinde satıcıyükümlüğünün temeli sözleşmede taahhüt ettiği malı, doğru zamanda,doğru yerde ve sözleşmede taraflarca kararlaştırılan vasıflarda alıcıyateslim etmesidir. Satım sözleşmesinin ihlali durumunda alıcıya tanınanhaklar ile ilgili hükümler yorumlanırken, taraflar satış sözleşmesini oluşturdukları dönemde ürünün nitelikleri ve alıcının beklentileri açıkça ifade edilmesi ve hükme bağlanması önerilmektedir.

The United Nations International Goods Contracts (CISG) are a multilateral treaty that creates a uniform framework for international trade. It aims to trade by creating equal and modern ground rules in all countries, regardless of their legal traditions or their levels of economic development. In this study, the rights that the buyer will have if the seller neglects the VSS contract are examined. The basis of the seller's obliga tion in this sales contract is to deliver the contractual goods to the buyer at the right time, in the right place and with the qualifications determi ned by the parties. When interpreting the provisions relating to the rights granted to the buyer in the event of violation of the sales contract, it is recommended that the qualities of the product and the expectations of the buyer be clearly stated in the period during which they form the sales contract.
STUDIES ON THE RIGHTS OF THE BUYER IN THE EVENT OF VIOLATION OF THE CONTRACT OF SALE BY THE SELLER UNDER THE VIENNA SALES CONVENTION (CISG)
Keywords: sözleşme; satıcı; haklar; ekonomi